Surgical treatment of mitral narrowness: our experience - Sanjinés, Aníbal; Dighiero, Jorge; Hazán, Jacobo; Canabal, Eduardo J; Horjales, José O; Aguirre, César V (Cirugía del Uruguay, 2020)
Presented at session 14th October 1955